Variations in the physical demands and technical performance of professional soccer teams over three consecutive seasons - Akyildiz, Z.; Nobari, H.; González-Fernández, F. T.; Moreira Praça, G.; Sarmento, H.; Hikmet Guler, A.; Kaan Saka, E.; Clemente, F. M.; Figueiredo, A. J. (Scientific Reports, 2022)
The purpose of this study was twofold: (i) to analyze the seasonal variations in the physical demands of Turkish Super League teams considering their status in the final rankings and (ii) to analyze the seasonal variations in the technical performance of Turkish Super League teams considering their status in the final rankings. This study followed an observational analytic retrospective design. In the last three seasons of the Turkish Super League (2015-2016, 2016-2017 and 2017-2018), 918 football matches, 54 teams, 25,029 observations were made. The Sentio Sports optical tracking system was used to quantify the physical demands and technical execution of players in all matches. No significant differences of external load were found between seasons analyzed (p > 0.05). The number of lost balls, ball touches in the central corridor, and goals from set pieces increased from season one to the others (p < 0.05), while the number of successful dribbles reduced over time (p < 0.05). As conclusion, it seems not occurred a progressive change in external load over the seasons, while an evolutionary trends regarding technical variables were observed.